2019 IEEE/CVF Conference on Computer Vision and Pattern Recognition (CVPR) 2019
DOI: 10.1109/cvpr.2019.00255
|View full text |Cite
|
Sign up to set email alerts
|

Inverse Path Tracing for Joint Material and Lighting Estimation

Abstract: Inverse Path Tracing Roughness Emission Albedo Rendering Geometry & Target ViewsFigure 1: Our Inverse Path Tracing algorithm takes as input a 3D scene and up to several RGB images (left), and estimates material as well as the lighting parameters of the scene. The main contribution of our approach is the formulation of an end-to-end differentiable inverse Monte Carlo renderer which is utilized in a nested stochastic gradient descent optimization. AbstractModern computer vision algorithms have brought significan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
39
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
3
2

Relationship

1
9

Authors

Journals

citations
Cited by 102 publications
(43 citation statements)
references
References 31 publications
0
39
0
Order By: Relevance
“…Nguyen-Phuoc et al [2018] and Insafutdinov and Dosovitskiy [2018] propose neural DRs using a volumetric shape representation, but the resolution is limited in practice. and Azinović et al [2019] introduce a differentiable ray tracer to implement the differentiability of physics based rendering effects, handling e.g. camera position, lighting and texture.…”
Section: Differentiable Renderingmentioning
confidence: 99%
“…Nguyen-Phuoc et al [2018] and Insafutdinov and Dosovitskiy [2018] propose neural DRs using a volumetric shape representation, but the resolution is limited in practice. and Azinović et al [2019] introduce a differentiable ray tracer to implement the differentiability of physics based rendering effects, handling e.g. camera position, lighting and texture.…”
Section: Differentiable Renderingmentioning
confidence: 99%
“…Our current implementation sorts the evaluation locations by their Z-order to create coherent access, however for large images the cost of sorting is non negligible. Finally, the boundary sampling complicates selective evaluation of the pixel colors: consider a pixel-wise loss function, we can stochastically evaluate the loss function and gradients by randomly choosing the pixel locations we want to evaluate, and this significantly speeds up the gradient descent procedure [Azinović et al 2019]. Unfortunately, boundary sampling makes selective evaluation difficult: we need to sample the intersection of the boundaries and the selected pixels' filter support area.…”
Section: Discussionmentioning
confidence: 99%
“…However, we use a non-parameteric representation and therefore we can generalize to non-symmetric point-lights with arbitrary patterns and colors. Also in air, Azinovic et al [4] infer light source positions in a rasterization based inverse rendering scheme, which however does not extend to volumetric effects such as attenuation and scattering. Also the general concept of analysis-throughsynthesis, or inverse rendering, for obtaining optical parameters has been proposed before in air using rasterization techniques and several simulation studies have suggested that raytracing-based solutions could be useful for volumetric parameters as well [10,34,31].…”
Section: Related Workmentioning
confidence: 99%